High-Resolution Morphological Characterization Investigation On The Effects Of Local Malaysian Condiments On Human Mineralized Tissues. - Che Ghazali, Farid; Wan Muda, Prof Dr Wan Abdul Manan; Mat Asan, En Jamaruddin (2002)
There are a huge variety of locally produced Malaysian sauces available in the local market. In many instances they may formed the everyday condiments of the main menu especially during lunch and dinner to the local Malaysian citizen.